2019
DOI: 10.1177/0269881119844186
|View full text |Cite
|
Sign up to set email alerts
|

Mitragynine (Kratom) impairs spatial learning and hippocampal synaptic transmission in rats

Abstract: Background: Mitragynine is the major alkaloid of Mitragyna speciosa (Korth.) or Kratom, a psychoactive plant widely abused in Southeast Asia. While addictive effects of the substance are emerging, adverse cognitive effects of this drug and neuropharmacological actions are insufficiently understood. Aims: In the present study, we investigated the effects of mitragynine on spatial learning and synaptic transmission in the CA1 region of the hippocampus. Methods: Male Sprague Dawley rats received daily (for 12 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 60 publications
5
37
0
1
Order By: Relevance
“…Here we report that the main psychoactive alkaloid of the kratom plant, mitragynine, mitigates morphine withdrawal symptoms. Although preclinical studies have shown that mitragynine may have an abuse potential and adverse cognitive effects by itself (23,36,43,64), field studies have shown that these effects emerge usually at doses way higher than what humans voluntarily consume (65,66). In addition, we did not find negative effects of mitragynine substitution on hematological, biochemical, and tissue level in this study, which confirms field studies that report mild impairments even after long term chronic use (67,68).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here we report that the main psychoactive alkaloid of the kratom plant, mitragynine, mitigates morphine withdrawal symptoms. Although preclinical studies have shown that mitragynine may have an abuse potential and adverse cognitive effects by itself (23,36,43,64), field studies have shown that these effects emerge usually at doses way higher than what humans voluntarily consume (65,66). In addition, we did not find negative effects of mitragynine substitution on hematological, biochemical, and tissue level in this study, which confirms field studies that report mild impairments even after long term chronic use (67,68).…”
Section: Discussionsupporting
confidence: 83%
“…Purified mitragynine was confirmed by high-performance liquid chromatography (HPLC) and proton nuclear magnetic resonance (1H-NMR) (400 MHz) analysis (35). Mitragynine obtained by this procedure was approximately 98% pure (36).…”
Section: Drug Preparationmentioning
confidence: 93%
“…We did not see a mitragynine-induced change in theta-gamma coupling between the HIP and cortical regions; however, disruption of cortical patterns may independently have potential negative impacts on cognitive processes such as learning and memory. Indeed, both mitragynine and morphine similarly impact on learning and memory processes with both drugs shown to impair both spatial and reversal learning in rodents (Apryani et al, 2010; Brolin et al, 2018; Hassan et al, 2019; Ismail et al, 2017; Lu et al, 2010; Yusoff et al, 2016). However, it is of importance that the present findings do not identify the mechanism by which the observed mitragynine-induced oscillatory changes occurred, which may be entirely independent of MOR activation, and distinct from morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chronic mitragynine administration in rodents has been reported to impair acquisition, consolidation and retrieval of passive avoidance learning (Yusoff et al, 2016), enhance punishment resistance during reward seeking and impair place learning (Ismail et al, 2017), as well as diminish working memory and reduce locomotor activity (Apryani et al, 2010). Mitragynine has also been shown to impair spatial learning in the Morris water maze (Hassan et al, 2019). Additionally, anxiety-like behaviours in rodents have been found to improve with acute mitragynine administration (Hazim et al, 2011, 2014) and antidepressant-like effects associated with mitragynine administration have been demonstrated in a murine model system of depression (Idayu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has only weak euphoric effects in the dose range humans voluntarily use ( Singh et al., 2019b ) and is not associated with neurological or psychiatric deficits and addiction development in the vast majority of regular users in Malaysia ( Singh et al., 2015 , 2018a ; 2018b ; Leong Bin Abdullah et al., 2019 ). However, in preclinical studies we showed that its main alkaloid mitragynine can at high doses have reinforcing effects and induce addiction-like behavior with adverse cognitive effects in rodents ( Yusoff et al., 2016 ; Ismail et al., 2017 ; Hassan et al., 2019 ). These effects are partly mediated by an opiate-like mechanism ( Stolt et al., 2014 ; Yusoff et al., 2017 ; Obeng et al., 2020 ), but may also involve other targets in the brain ( Yusoff et al., 2018 ; Hiranita et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%